Time use and macroeconomic uncertainty - Matteo Cacciatore; Stefano Gnocchi; Daniela Hauser (Bank of Canada, 2023)
We estimate the effects of economic uncertainty on time use and discuss its macroeconomic implications. Using data from the American Time Use Survey, we first infer cyclical variation in home production and leisure time. We then document that higher uncertainty increases housework and reduces market hours worked, with modest effects on leisure. Finally, we propose a model of housework with time-varying uncertainty that quantitatively accounts for these results. We use the model to demonstrate that substitution between market and non-market work provides an additional insurance margin to households, weakening precautionary savings and labor supply. However, time-use reallocation also lowers aggregate demand, ultimately amplifying the contractionary effects of uncertainty. Policies that reallocate time use toward housework (e.g., lockdown restrictions) amplify the recessionary effects of uncertainty and can result in aggregate dynamics consistent with a supply-side shock.
Keywords: E24; E32; E52; J22; 330; Business fluctuations and cycles; Domestic demand and components; Coronavirus disease (COVID-19); Monetary policy and uncertainty